Controlling water transport in carbon nanotubes - Goh, Kunli (2017)
Water transport inside carbon nanotubes (CNTs) shows a wealth of unique nanofluidic phenomena, which can be exploited as solutions for many global challenges. However, translating this potential into practical applications remains questionable to date. Recently, a work by Secchi and coworkers provides confirmatory evidence of radius-dependent water slippage inside an individual CNT. This article therefore puts into perspective two key takeaways, namely, nanoconfinement and electronic structures of CNT, as promising approaches to control ultrafast water transport inside CNTs.